Penerapan Undang-Undang Nomor 21 Tahun 2019 Tentang Karantina Hewan, Ikan Dan Tumbuhan terhadap Tindak Pidana Pemasukan Sarang Burung Walet Ilegal Dari Malaysia Ke Tanjung Balai Asahan - Priyadi Priyadi; Suhaidi Suhaidi; Isnaini Isnaini (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to determine the regulation and application of the law on the importation of swallow's nests; and Quarantine investigator strategies to maximize the implementation of quarantine regulations. The research method used in this study is normative juridical with a case approach and legislation with data collection techniques, namely documentation studies and interviews with descriptive data analysis. This study shows the results that the regulation of the entry of Swallow's Nest refers to Law no. 21 of 2019 concerning Animal, Fish and Plant Quarantine and Regulation of the Minister of Agriculture Number 26 of 2020 concerning Animal Quarantine Measures Against the Importation or Exportation of Swallow's Nests To and From Within the Territory of the Unitary State of the Republic of Indonesia. In its application, there are problems, namely the sentence to the defendant is only 4 months and a fine of 6 million rupiah which is considered too low when compared to the threat of Article 86 of Law no. 21 of 2019 which is 10 years and a fine of 10 billion. Juridical efforts to maximize the application of quarantine regulations are recommended to immediately issue derivative regulations such as Government Regulations, increase the status of Quarantine UPT at least to the level of Balai and create special functions for vigilance.